The analysis of chlorophyll-a distribution in fishing areas of Aceh Waters - Muhammad Riandi; Muhammad Irham; Muhammad Rusdi; Anwar Deli; Faisal Abdullah; Edy Miswar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
The distribution and abundance of fish are strongly influenced by several oceanographic parameters, one of which is chlorophyll-a. Chlorophyll-a is one of the oceanographic parameters that play an important role in primary productivity in the sea. The distribution of chlorophyll-a contained in phytoplankton can be used as a measure of fertility in water. With advances in geographic information systems or remote sensing, the distribution of chlorophyll-a can be used to estimate fish catchment areas. This study aims to look at the distribution of chlorophyll-a in Aceh waters both spatially and temporally to predict fishing locations. This study used satellite imagery combined with a Geographic Information System (GIS) to detect chlorophyll-a’s distribution. The results of satellite image processing show that the average monthly value of chlorophyll-a in Aceh waters ranges from 2.71 – 23.54 mg/m3, areas with high chlorophyll-a are generally located in the western waters of Aceh to the southwestern waters of Aceh, while areas with The lowest chlorophyll-a is generally in areas far from the coast (towards the open sea) with a range of 0.04 – 0.5 mg/m3 where the lowest average occurs in the east monsoon. However, in general, the potential locations for fishing grounds are more in the waters west of Aceh than in the waters north of Aceh, Aceh waters.Keywords:Chlorophyll-aSatellite imageFishing areaGeographic information SystemAceh Waters